The influence of problem-based physics learning using guided inquiry toward scientific attitude - Effendi Effendi; Thoha Firdaus; Erwin Erwin (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The process of physics learning should be carried out by scientific investigation or discovery, in order to grow the ability to think critically and be scientific so that it can solve the problem. This study aims to determine the influence of guided inquiry method on scientific attitude. This research is experimental research that is experiment class using problem solving method and control class using lecture method. The number of samples taken 60 respondents from a total of 120 respondents. Data collection techniques using questionnaires and hypothesis test research using t test. From the results of research indicate that there is influence of guided inquiry method toward scientific attitude, because t test shows tcount = 5.994 and ttable = 2,004.